The Encyclopedia of LGBTQIA+ Portrayals in American Film - Dymond, Erica Joan; Murguía, Salvador Jiménez (Rowman & Littlefield Publishers, 2022)
"A valuable reference guide for film collections and LGBTQIA+ studies." — Library Journal, Starred Review The depictions of LGBTQIA+ characters in film have always varied immensely. However, the negative depictions often seem to outweigh the positive, perhaps because of the hurt they inspire or perhaps because they regrettably outnumber the positive films. The Encyclopedia of LGBTQIA+ Portrayals in American Film explores works from the past fifty years in order to not only discuss how LGBTQIA+ characters are portrayed in American film, but also how these portrayals affect viewers. Contributors to this valuable reference include film and media scholars, gender studies scholars, journalists, LGBTQIA+ advocates, and more, representing countries from around the world. This rich array of perspectives provide careful and critical examinations of more than 100 films, ranging from the ethical and compassionate to the deliberately cruel and destructive. Featuring films such as American Beauty, Batman v Superman, Fight Club, The Grand Budapest Hotel, Little Miss Sunshine, and Venom, this extensive volume informs and educates scholars and general readers alike, guiding them to see injustice more clearly and inspiring future generations to create art that is both inclusive and thoughtful.